A study on the reproduction of local zebu and F1 crossbred (European x zebu) cows. I. Number of services per conception, gestation length and days open till conception - Tegegne, Azage; Galal, E.S.E.; Kebede, B. (1981)
The reproductive performance of Boran, Horro and Barka cattle and their F1 crosses with Friesian, Jersey and Simmental breeds at 4 research stations was investigated. The environmental conditions covered in the study represented wet and dry conditions. Detailed information provided on the number of services required for successful conception, gestation length and number of days between parturition and subsequent conception.